Amobilisasi Eceng Gondok (Eichhornia crassipes) dalam Silika Gel untuk Penyerapan Ion Logam Kadmium - Linda, Roza (Jurnal Pilar Sains, 2005)
Eichhornia crassipes was successfully used in adsorption procedure that removedcadmium from aqueous solution. Several parameters that can affect metal uptake such asparticle size, pH, metal in concentration and time of heat were described. Based onresearch it was found optimal condition adsorption of Cadmium at particle size 250micrometer, ratio Eichhornia crassipes silica gel 3:1, pH 7, Cd ion concentration 200ppm,and heating time 45 minutes. Efficiency adsorption optimal at optimal condition are99.0025%. The method was applied to adsorption cadmium in waste water.